2018
DOI: 10.3390/fib6040069
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of High-Performance Yarns Transversely Loaded by Different Indenters

Abstract: In this study, we performed off-axis transverse loading experiments to study the stress concentration developed in a high-performance yarn with different indenters. A universal testing machine was utilized to perform quasi-static transverse loading experiments on Twaron® yarns. Seven different round indenters possessing radius of curvature ranging from 0.20 to 4.50 mm were employed in the experiments. In addition, post-mortem failure analysis was performed on the recovered specimens via a scanning electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…A possible reason for the Smith theory to overestimate the critical velocity is that the theory assumes bending is negligible [9,10,12]. Later in the results section, we showed that when the yarn was impacted by a razor blade above the critical velocity, the yarn deflection was small prior to rupture.…”
Section: Euler-bernoulli Beam Modelmentioning
confidence: 83%
See 4 more Smart Citations
“…A possible reason for the Smith theory to overestimate the critical velocity is that the theory assumes bending is negligible [9,10,12]. Later in the results section, we showed that when the yarn was impacted by a razor blade above the critical velocity, the yarn deflection was small prior to rupture.…”
Section: Euler-bernoulli Beam Modelmentioning
confidence: 83%
“…The yarn specimens used in this study were strands of Twaron ® 2040 yarns extracted from plain weave single ply CT 709 Twaron ® in the warp direction. The quasi-static mechanical properties of this yarn were determined in previous studies and are tabulated in Table 1 [12,13]. Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations